2023
DOI: 10.1007/s40620-023-01596-x
|View full text |Cite
|
Sign up to set email alerts
|

Risks of in-hospital death and hospital length of stay of 7 days or longer among end-stage renal disease patients hospitalized with COVID-19: a retrospective cohort study in five California medical centers

Abstract: Patients with pre-existing chronic health conditions, including End-Stage Renal Disease (ESRD) requiring dialysis, are at high risk for hospitalization with COVID-19. Kidney failure leads to a poorly regulated immune system [1], and susceptibility to infections, which is the second most reported cause of death in the ESRD population.Studies of hospitalized ESRD patients early in the COVID-19 pandemic have reached different conclusions, with some finding that ESRD conveys an independent risk for in-hospital dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, recent studies argue against this finding. In the first recent study, the authors found that without adjustment, ESKD patients hospitalized for COVID-19 had a significantly higher odds of in-hospital death than patients without ESKD, but once comprehensively adjusted, there was no excess risk of death for ESRD patients 10 . In the second study, the authors found that among individuals with COVID-19-positive test result, ESKD patients did not have a higher odd for adverse outcomes (mortality, stroke, shock, intubation, sepsis, pneumonia) compared with matched individuals without ESKD 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies argue against this finding. In the first recent study, the authors found that without adjustment, ESKD patients hospitalized for COVID-19 had a significantly higher odds of in-hospital death than patients without ESKD, but once comprehensively adjusted, there was no excess risk of death for ESRD patients 10 . In the second study, the authors found that among individuals with COVID-19-positive test result, ESKD patients did not have a higher odd for adverse outcomes (mortality, stroke, shock, intubation, sepsis, pneumonia) compared with matched individuals without ESKD 11 .…”
Section: Introductionmentioning
confidence: 99%